Glacial Expansion or Interglacial Expansion? Contrasting Demographic Models of Four Cold-Adapted Fir Species in North America and East Asia - Shao, Yi-Zhen; Yuan, Zhi-Liang; Liu, Yan-Yan; Liu, Feng-Qin; Xiang, Rui-Chen; Zhang, Yuan-Yuan; Ye, Yong-Zhong; Chen, Yun; Wen, Qian (Frontiers in Ecology and Evolution, 2022)
Understanding and forecasting species’ response to climate change is a critical need for future conservation and management. Two expansion hypotheses, the glacial expansion versus the interglacial expansion, have been proposed to interpret how cold-adapted organisms in the northern hemisphere respond to Quaternary climatic fluctuations. To test these two hypotheses, we originally used two pairs of high-low elevation firs from North America (A. lasiocarpa and A. balsamea) and East Asia (A. chensiensis and A. nephrolepis). A. lasiocarpa and A. chensiensis are widely distributed in high-elevation regions of western North America and central China. A. balsamea and A. nephrolepis occur in central North America and northeast China, with much lower elevations. These fir species are typical cold-adapted species and sensitive to climate fluctuations. Here, we integrated the mtDNA and cpDNA polymorphisms involving 44 populations and 585 individuals. Based on phylogeographic analyses, recent historical range expansions were indicated in two high-elevation firs (A. lasiocarpa and A. chensiensis) during the last glaciation (43.8-28.4 or 21.9-14.2 kya, 53.1-34.5 or 26.6-17.2 kya). Such glacial expansions in high-elevation firs were further confirmed by the evidence of species distribution modelling, geographic-driven genetic patterns, palynological records, and current distribution patterns. Unlike the north American firs, the SDM models indicated unremarkable expansion or contraction in East Asia firs for its much more stable conditions during different historical periods. Taken together, our findings highly supported that high-elevation firs experienced glacial expansion during the Quaternary climate change in East Asia and North America, as interglacial expansion within low-elevation firs. Under this situation, the critically endangered fir species distributed in high elevation would have no enough higher elevational space to migrate. Facing the increasing global warming, thus we proposed ex-situ conservation of defining conservation units as the most meaningful strategy.